PENGARUH KEADILAN ORGANISASI TERHADAP KOMITMEN ORGANISASIONAL DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING DI SEKOLAH SANTA URSULA BSD - Catur Agus Sancoko; Mutiara S Panggabean (Universitas Mercu Buana, 2015)
Abstract: The purpose of this study is to investigate and analyze the influence of organizational justice on job satisfaction, organizational justice influence on organizational commitment directly, the influence of organizational justice on organizational commitment intervening variable of job satisfaction, as well as the effect of job satisfaction on organizational commitment. The method used is descriptive method using questionnaires for data gathering. The population in this study were all employees of the school Santa Ursula BSD consisting of education and non-education employees. Analysis of the data used is the SEM analysis with path analysis method. Based on the results of this study concluded that the three dimensions of organizational justice, namely distributive justice,procedural justice, and interactional justice give positive and significant effects with job satisfaction. These three dimensions of organizational justice give positive effects but not significant with organizational commitment. Employee job satisfaction gives positive and significant effect with organizational commitment. These three dimensions of organizational justice give positive and significant effects with organizational commitment through employee job satisfaction, in which interactional justice has the most powerful influence than the other dimensions.Keywords: Organizational Justice, Job Satisfaction, Organizational Commitment